Estimates of genetic variances in Striga resistant extraearlymaturing maize populations - Badu-Apraku, Baffour (Informa UK Limited, 2006)
Breeders should maintain sufficient genetic variability in a population to ensure continuous advance from selection for a target trait. The extra-early-maturing Striga resistant/tolerant maize (Zea mays L.) populations, TZEE-W Pop DT STR (white) and TZEE-Y STR (yellow), have each gone through three cycles of S1 recurrent selection for improvement for grain yield, Striga resistance under artificial Striga infestation, and other desirable agronomic characters. S1 families derived from cycle 3 of each population were evaluated at Mokwa and Abuja in Nigeria in 2003 under artificial Striga hermonthica infestation. The objectives of this study were to determine the genetic variability, herita-bilities, and genetic advance among traits associated with Striga resistance in each population. Results showed that the estimates of genetic variance, a 2 were moderate to large for most traits of TZEE-W Pop STR C3 with the exception of husk cover and Striga emergence count at 8 and 10 weeks after planting (WAP). Out of 13 traits of TZEE-Y Pop STR C3, 7 had moderate-to-large genetic variances whereas the others were much lower. Broad-sense heritability estimates of traits in TZEE-Y Pop STR C3 were moderate-to-large for days to silking and anthesis; other traits had generally low heritabilities (<0.50). On the other hand, heritability estimates in TZEE-W Pop STR C3 were moderate-to-large for days to anthesis and plant height, and generally low for the other traits. The percentage predicted gain from selection for the traits of TZEE-Y Pop STR C3 ranged from 2.82 for Striga damage rating at 8 WAP to 22 for grain yield; the percentage gain for grain yield of TZEE-W Pop STR C3 was 25 and 0.37–39.21 for 12 other traits. Highly significant positive or negative phenotypic correlations were detected between grain yield and most other traits for TZEE-W Pop STR C3. The correlations between grain yield and other traits of TZEE-Y Pop STR C3 followed trends similar to those of TZEE-W Pop STR C3. The results suggest that sufficient residual genetic variability still exists in each population to allow good progress from further selection for grain yield and Striga resistance.